Middleton, Colonial America - A History, 1565-1776 - Rico, Monica (Teaching History: A Journal of Methods, 2004)
This third edition of Colonial America contains a new chapter on Spanish and French colonization of continental North America, although the focus remains on the English colonies. Middleton has also retained the divided organizational structure employed in earlier editions. Colonial America treats the colonies chronologically up through the end of the seventeenth century and then turns to a thematic treatment of "provincial America" during the eighteenth century before concluding his book with two chapters on the revolutionary crisis leading to independence. The revised and updated bibliography serves as a competent guide to recent work as well as a few old classics.